Universal grammar: arguments for its existence - Umarlebbe, Jameela Hanoon (Australian International Academic Centre PTY. LTD., 2021)
The first part of this paper discusses the rationale for universal grammar (UG) theory to explain first language acquisition. It also illustrates the issues of language acquisition Chomsky argued which could not be supported by behaviourist theories and shows how Chomsky proposed a solution to this problem through his theoretical model of universal grammar. The next part outlines this theory’s key tenets, arguing that these principles must be an innate endowment of the human mind. Moreover, the study illustrates specific examples of grammatical phenomena that universal grammar seeks to explain. Lastly, it shows that certain distinct grammatical features are linked and that these connections can be explained within the Universal Grammar theoretical framework. The only reasonable explanation for the first language learning needs only limited linguistic exposure to activate them and set criteria for the language being learned for children whose minds have already been wired with essential language concepts.